0009 Asbestosis and Exposure Levels in a Chinese Asbestos Worker Cohort. (23rd June 2014) - Wang, Xiaorong; Courtice, Midori N; Lin, Sihao; Qiu, Hong; Yu, Ignatius TS
Abstract : Objectives: To assess the relationship between quantitative exposure levels and the development of asbestosis in a Chinese asbestos worker cohort. Method: A cohort consisting of 577 male workers from an asbestos products factory in China was followed for 37-years. Personal information was collected, including date of hire, specific job types, duration of exposure, and smoking habits. There were 127 workers (22%) diagnosed as asbestosis by a specialised panel using Chinese radiographic Diagnostic Criteria for Pneumoconioses (GB5908–86). Individual cumulative fibre exposures (f-yrs/ml) were estimated based on periodic dust/fibre measurements from different workshops and years of working at specific workshops, and then categorised into four levels (quartile). The relationship between the exposure levels and cumulative incidence of asbestosis was assessed with Cox Proportional Hazard Model, adjusting for age and smoking. Results: Workers at the four exposure levels were comparable in age at entry, exposure duration (around 25 yrs), and smoking rate. However, the proportion of asbestosis cases was grater with exposure levels, accounting for 9%, 27%, 29% and 36% from 1 st quartile to 4 th quartile, respectively. Hazard ratios for cumulative incidence of asbestosis showed a clear trend with the exposure levels, with a nearly three-fold increase (3.42. 95% CI 2.0, 5.9) at the highest exposure level, compared to at the lowest level. Conclusions: The study using quantitative estimate of exposures, which was seldom available in China, provides additional evidence for the exposure-response relationship between chrysotile exposure and the development of asbestosis in asbestos workers.